2016
DOI: 10.1002/adhm.201600718
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Anticancer Effect of Peptide‐Docetaxel Nanoassembly Targeted to Tubulin: Toward Development of Dual Warhead Containing Nanomedicine

Abstract: Microtubule dynamics play a crucial role in cancer cell division. Various drugs are developed to target microtubule. Although a few of them show potential in treatment of cancer, but success rate is limited due to their poor bioavailability and lack of specificity. Thus, development of highly bioavailable and target specific anticancer drug is extremely necessary. To address these key issues, here, a combination of approaches such as development of a dodecapeptide-docetaxel nanoassembly targeted to tubulin and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 84 publications
0
32
0
Order By: Relevance
“…Microtubules are hollow tubular protein assemblies composed of intracellular α-/β- tubulin dimers with significant nanodevice implications attributed to their involvement in many eukaryotic cell functions including tumor progression. Peptide-modulated nanodevice-encapsulating drugs targeting intracellular tubulins under different formulations such as peptide-conjugating liposomes or peptide-drug assemblies to exert synergistic anti-cancer effects have attracted vast attentions [88,89]. A recent pioneer study further demonstrated that peptides selected from microtubule-associated protein Tau functionalized inner surface of microtubule by encapsulation of gold nanoparticles inside microtubules [90].…”
Section: Innovations and Computational Methods For Peptide—proteinmentioning
confidence: 99%
“…Microtubules are hollow tubular protein assemblies composed of intracellular α-/β- tubulin dimers with significant nanodevice implications attributed to their involvement in many eukaryotic cell functions including tumor progression. Peptide-modulated nanodevice-encapsulating drugs targeting intracellular tubulins under different formulations such as peptide-conjugating liposomes or peptide-drug assemblies to exert synergistic anti-cancer effects have attracted vast attentions [88,89]. A recent pioneer study further demonstrated that peptides selected from microtubule-associated protein Tau functionalized inner surface of microtubule by encapsulation of gold nanoparticles inside microtubules [90].…”
Section: Innovations and Computational Methods For Peptide—proteinmentioning
confidence: 99%
“…20,21 Since the seminal report on use of graphene oxide (GO), a derivative of graphene, this compound has seen increasing application in biomedical areas, including cell proliferation and differentiation, drug delivery, immune response, and anticancer therapy. 15,18,20,[22][23][24] Significantly, GO has abundant oxygen functional groups, including hydroxyl, epoxy, carbonyl, and carboxyl groups. 25 The effect of GO can be modulated by modification of its oxygen moieties as well as altering chemical functionality on graphene layers.…”
Section: Introductionmentioning
confidence: 99%
“…There are two advantages of following this procedure; first, proposed chemicals may improve the performance of ACPs by decreasing the level of HS and CS at the cell surface and second, diminishing the utilization cost of ACPs by reducing the required dose of consumption. The same efforts with promising outcomes have been done in vitro [33,34] and in silico studies. [35] With regard to the effect of GAGs on performance of therapeutic peptides, Fadnes et al [17] clearly showed the negative effect of HS and CS on performance of bovine lactoferricin (LfcinB) and the designer peptide, KW5, as cationic therapeutic peptides.…”
Section: Discussionmentioning
confidence: 96%